2003
DOI: 10.1002/cb.119
|View full text |Cite
|
Sign up to set email alerts
|

The qualitative impact of broadcast media advertisement on the perception of medicines in Nigeria

Abstract: The study was aimed at determining the qualitative impact of broadcast media (radio and television) advertisement on the perception of medicines among the adult population in Nigeria. The study was carried out in Ibadan using a carefully designed and pretested questionnaire as the instrument for data collection after obtaining necessary ethical clearance. The study showed that broadcast media had a positive influence on the population. Both media were found to create awareness and enhance the existing level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This corroborates the result obtained from the oral interview where 64 % of the respondents posited that increase in educational level of students may not help reduce the incidence of self-medication and its attendant prevalence. This may be attributed to some extraneous factors such as advertisement or peer group influence, poverty or financial constraints, weak regulation of medicines which facilitates easy access to drugs, long waiting queues at clinics or hospitals, among others [2,7,8,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corroborates the result obtained from the oral interview where 64 % of the respondents posited that increase in educational level of students may not help reduce the incidence of self-medication and its attendant prevalence. This may be attributed to some extraneous factors such as advertisement or peer group influence, poverty or financial constraints, weak regulation of medicines which facilitates easy access to drugs, long waiting queues at clinics or hospitals, among others [2,7,8,14].…”
Section: Discussionmentioning
confidence: 99%
“…Self-medication, could cause bacteria resistance to such antibiotics and may precipitate the emergence of multipleresistant organisms that would be difficult to treat and this has caused increased morbidity [3][4][5][6]. Perception of illness and incessant advertising, among others, have increased the prevalence of self-medication which accounts for about 2.9 -3.7 % causes of death in hospitals as a result of drug-drug interactions [7][8][9][10][11][12][13]. It has also been reported that drug use is influenced by the sociodemographic characteristics of drug consumers such as gender, morbidity, age, attitudes about life and health, stress, and social roles but has nothing to do with education and ethnicity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Medicines which are commonly used for self-medication include analgesics, anti-malarials, antibiotics and cough syrups 3 . Perception of illness is one of the factors that has increased the prevalence of self-medication, which accounts for about 2.9 -3.7 % causes of death in hospitals as a result of drugdrug interactions 4 . The variation in the prevalence of self-medication among developing and developed nations can be caused by disparities in health care systems such as reimbursement policies, access to health care, and drug dispensing policies 5 .…”
Section: Introductionmentioning
confidence: 99%